A subinterval dimension-wise method for robust topology optimization of structures with truss-like lattice material under unknown but bounded uncertainties - Liu, Dongliang; Qiu, Zhiping (Structural and multidisciplinary optimization, 2021)
The robust topology optimization of structures with truss-like lattice material under unknown but bounded uncertainties is studied in this paper. To consider the uncertainty of structures composed of truss-like lattice material during the production and service, a formulation of robust topology optimization is constructed, which takes into account the unknown but bounded uncertainties of both the magnitude and direction of load and the diameter of truss-like lattice material. Besides, the absolute robustness index and the relative robustness index are established to measure the robustness of the structure. By dividing the intervals of uncertain parameters, a method called the subinterval dimension-wise method is proposed to solve the difficulty of determining the response interval of structures caused by large uncertainty. Finally, two examples are given to illustrate the effectiveness of the proposed method and its applicability in complex structures, especially the structure with large uncertainty.